Protein levels for heat-exposed broilers: Performance, nutrients digestibility, and energy and protein metabolism - Faria Filho, Daniel Emygdio de; Campos, Daniel Mendes Borges [UNESP]; Alfonso-Torres, Karoll Andrea [UNESP]; Vieira, Bruno Serpa [UNESP]; Rosa, Paulo Sérgio; Vaz, Aiani Maria [UNESP]; Macari, Marcos [UNESP]; Furlan, Renato Luis [UNESP] (My University, 2007)
Heat stress causes significant economic losses on broilers production due to poorer performance and carcass quality. Considering that protein has the highest heat increment among nutrients, it has been suggested that protein levels should be reduced in diets for heat-exposed broilers. Nevertheless, there are no conclusive results on the benefits of such practice, and further studies should be performed to elucidate some reported discrepancies. Thus, a trial was carried out to evaluate the effects of dietary protein levels (17, 20 and 23%) and environmental temperature (22 and 32°C) on the performance, nutrients digestibility, and energy and protein metabolism of broiler chickens from 21 to 42 days of age. Nutrients digestibility was determined by total excreta collection, and energy and protein metabolism was evaluated by comparative slaughter method. It was concluded that (1) heat exposure impairs broilers performance and increases nitrogen excretion, but do not change nutrients digestibility; (2) high-protein diets are technically feasible and promotes lower heat production for broilers reared under thermoneutral or hot environments, however, high-protein diets increases nitrogen excretion. © Asian Network for Scientific Information, 2007.
Keywords: Comparative slaughter; Heat stress; Ideal protein; Nitrogen excretion; Total excreta collection; Gallus gallus